Evaluation of the Properties of Bituminous Concrete Prepared from Brick-Stone Mix Aggregate - Dipankar Sarkar; Manish Pal; Ashoke K. Sarkar; Umesh Mishra (Advances in Materials Science and Engineering)
The paper describes an investigation into mechanical properties of brick-stone bituminous concrete mix. The effect of brick-stone mix on various mechanical properties of the bituminous concrete such as Marshall stability, flow, Marshall Quotient (stability to flow ratio), Indirect Tensile Strength, stripping, rutting, and fatigue life of bituminous concrete overlay has been evaluated. In this study over-burnt brick aggregate (OBBA) and stone aggregate (SA) have been mixed in different ratios (by weight) such as 20 : 80, 40 : 60, 60 : 40, and 80 : 20, respectively. The laboratory results indicate that bituminous concrete, prepared by 20% brick aggregate and 80% stone aggregate, gives the highest Marshall stability. This bituminous concrete mix shows considerable improvement in various mechanical properties of the mix as compared to the other mixes.